Relationship of The Role of Superintended of Swallowing Drugs, Types of Treatment and Effective Cough with The Success of Treatment of Adult Pulmonary Tuberculosis - Maria Inceani Kase; Pius Weraman; Amelya B Sir (Journal of Health and Behavioral Science, 2022)
Tuberculosis is an infectious disease caused by the bacteria Mycobacterium tuberculosis. Treatment success was measured by looking at the number of all TB cases cured, and complete treatment among all TB cases treated and reported. This study aims to analyze the relationship between the role of Superintended Swallowing Drugs, type of treatment, and effective cough with successful treatment of adult pulmonary tuberculosis in the work area of the Oesapa Public Health Center in 2021. This type of research is a quantitative correlation with a cross-sectional study design. The sample consists of 134 people. Sampling was done by simple random sampling with a confidence level of = 0.05. The data analysis used was univariate and bivariate analysis with a chi-square statistical test. The results of this study indicate that there is a relationship between the role of Superintended of Swallowing Drugs and the success of adult pulmonary TB treatment (p-value = 0.024); there is a relationship between the type of treatment and the success of adult pulmonary TB treatment (p-value = 0.000), while there is no relationship between effective cough with successful treatment of adult pulmonary TB (p-value = 0.750).